LOCAL RE-OPERATION AND RECURRENCE IN ONCOPLASTIC BREAST SURGERY - Urban, Cicero; Amoroso, Vanessa; Lima, Rubens Silveira de (Mastology, 2017)
Introduction: In addition to a surgical option, the oncoplastic surgery (OP) is a new philosophy in the mammary oncologic therapy, since it combines concepts of oncologic surgery and plastic surgery. There was a concern that plastic surgery techniques would compromise the oncologic radicalism, leading to an increased risk of tumor recurrence and damage to the patients’ survival. The main purpose of the breast conservative surgery (BCS) is to obtain disease-free surgical margins, with a great esthetic-functional result. However, since the advent of this approach, the search for negative margins has been a problem. Despite the efforts to avoid compromised margins, they occur in 20 to 40% of the cases in the traditional BCS, and in many cases leading to the need of reexcision or even to mastectomy. Objective and method: In the analysis of recent studies, the OP role as a reduction factor of new surgeries and local recurrence is questioned. The aim of this paper is to analyze it based on literature review. Conclusion: According to recent studies, the OP became a safe oncological surgical technique that improves both the esthetic result and the disease local control, decreasing the compromised margins with impact on the mitigation of new surgeries rate.